Where is the disability? A critical analysis of case reports of online sexual abuse of children with disabilities - Gal Friedman-Hauser; Carmit Katz (Child Protection and Practice, 2025)
Background: Children with disabilities (CWD) face a heightened risk of experiencing sexual abuse. Despite the severity and persistence of these cases, they often receive inadequate responses from child protection systems compared to incidents involving non-disabled children. Moreover, recent technological advancements have extended the risk of sexual abuse beyond physical spaces to online environments. This creates an escalated risk and challenges for the protection of CWD. Objective: This study aims to conduct a qualitative-critical analysis of case reports detailing incidents of online child sexual abuse (OCSA) involving CWD to explore how these cases are documented and addressed. Participants and setting: The data comprised 25 reports from a hotline in Israel receiving reports of online child sexual abuse of CWD aged 11–17 across Israel. Methods: Influenced by a critical paradigm, the study utilizes a qualitative methodology to undertake a reflexive thematic analysis of the reports. Results: The analysis revealed a significant underrepresentation of CWD's voices in the reports, which predominantly reflected parental perspectives. Moreover, the disability aspect was often overlooked, with limited acknowledgment or reference to the child's disability. Conclusion: The findings underscored the marginalization of CWD in child protection processes. They highlighted the urgent need to integrate disability-specific considerations into post-abuse treatment and intervention, advocating for the inclusion of children's perspectives in reporting and response efforts. Recommendations include enhancing professional training, refining reporting protocols to address disability explicitly, and implementing policy reforms to ensure inclusive support systems. Future research should explore comparative analysis and gather qualitative insights from CWD to enhance intervention strategies effectively.